Evaluation of the Response of the Emergency Medical Service Department of the Palestinian Red Crescent Society for Crises and Disaster and its Effect on Quality of Service from the Service providers Prospective (Case Study: Great March of Return) - Azzam, Esraa Mosbah; Schokry, Abed Ahmed (Journal of Risk and Crisis Management, 2020)
The study aimed to evaluate the response of the Emergency Medical Service (EMS) Department in the Palestinian Red Crescent Society )PRCS) within the Gaza Strip to Great March of Return (GRM), and to investigate its impact on the quality of service, from the point of view of service providers, A mix between qualitative and quantitative research methods Was applied for this purpose. The researcher followed the method of comprehensive survey for all members of the study population. The self- developed questionnaire as a study instrument was distributed among the study population. 126 (from 139) questionnaires were retrieved (90.65%). Then the head of the EMS Department in Gaza as well as all participated branch- Managers of PRCS governorates of the Gaza Strip were interviewed. The data were analyzed using SPSS. The results of the study proved that the field of "Crisis and Disaster Response Planning" at the PRCS EMS Department was about (82.72%), while "availability of necessary information" was about (79.93%). The field of "training and further education of the employees" lay by (78.37%), and the area of "availability of material and human resources" on the other hand was about (79.84%), and the field of "teamwork" was about (74.33%). Looking at all sections of the study, the total score laid by (78.98%), which is not bad, taking into account, that the service providers are evaluating their own effort as well as work. According to those findings, the researcher recommended the need to involve service providers in the development of emergency plans, and the need to introduce further educational training in using modern techniques, as well as the encouragement of EMTs to participate in local and international conferences, and to initiate the coordination between the EMS Department of the PRCS and other health institutions in the healthcare sector within the Gaza Strip.